Identification of hub genes and pathophysiological mechanism related to acute unilateral vestibulopathy by integrated bioinformatics analysis - Cheng, Yajing; Zheng, Jianrong; Zhan, Ying; Liu, Cong; Lu, Bihua; Hu, Jun (Frontiers in Neurology, 2022)
Background: Although many pathological mechanisms and etiological hypotheses of Acute Unilateral Vestibulopathy (AUVP) have been reported, the actual etiology remains to be elucidated. Objective: This study was based on comprehensive bioinformatics to identify the critical genes of AUVP and explore its pathological mechanism. Methods: Gene expression profiles of AUVP and normal samples were from GSE146230 datasets of the Gene Expression Omnibus (GEO) database. Weighted gene co-expression network analysis (WGCNA) was constructed, and the WGCNA R-package extracted significant modules. The limma R-package was applied to identify differentially expressed genes (DEGs). The common genes of practical modules and DEGs were screened for GO and KEGG pathways analysis. The protein-protein interaction (PPI) layout and hub genes validation was created by Cytoscape software using the link from the STRING database. The functions of hub genes were predicted through the CTD (comparative genetics database) Results: The 332 common genes were screened from practical modules and DEG. Functional enrichment analysis revealed that these genes were predominantly associated with inflammation and infection. After construction of PPI, expressions of hub genes, and drawing ROC curves, LILRB2, FPR1, AQP9, and LILRA1 are highly expressed in AUVP (P＜0.05) and have a certain diagnostic efficacy for AUVP (AUC＞0.7), so they were selected as hub genes. The functions of hub genes suggested that the occurrence of AUVP may be related to inflammation, necrosis, hepatomegaly, and other conditions in CTD. Conclusion: LILRB2, FPR1, AQP9, and LILRA1 may play essential roles in developing AUVP, providing new ideas for diagnosing and treating AUVP.